POTENSI HASIL BERBAGAI VARIETAS UNGGUL BAWANG MERAH DI LAHAN ULTISOL KABUPATEN BANGKA - Kharolina Kharolina; Eries Dyah Mustikarini; Deni Pratama (Jurnal Tanah dan Sumberdaya Lahan, 2023)
High demand for shallots needs to be supported by an increase of yield in each region. The use of high-yield cultivar is one of the ways that can be done to increase the productivity of shallot conducted. Bangka has a soil of the Ultisol type, so adaptive cultivars on the land are indispensable. The research was carried out at the Experimental and Research Garden of Universitas Bangka Belitung. This study aims to determine the potential yield of onions and adaptive onion cultivars in Bangka Ultisol soil. The method used is a Randomized Block Design (RBD). Consists of 5 cultivars, such as Ambassador 1, Ambassador 2, Violetta, Keramat, and Maja Cipanas. Violetta is the most adaptive cultivar, that can grow to the height of the plant and the number of leaves that are almost equivalent to the onion plant planted in its native place. The onion cultivar that has the best yield potential to be grown in the Ultisol land of Bangka Regency is the Violetta cultivar because the weight of the bulbs and the number of bulbs produced are almost equivalent to the onion plants grown in their native area.